To measure the extent of balance in the elderly - Glòria Saüch; Marta Castañer; Raúl Hileno (FEADEF, 2013)
The programs of Physical Activity of municipal entitlement promote the physical exercise in the elderly. In this paper a procedure is contributed to value motor balance for the elderly by means of the standardized Tinetti scale that is used in geriatrics but not very common used in the Sciences of the Physical Activity and the Sport. We think that the use of this scale enriches the instrumentation for the evaluation of motor balance. The study has been applied to 90 participants that follow the municipal programs of physical activity for the elderly. The results obtained by means of parametric and non-parametric tests to compare independent groups reveals that motor balance maintains its optimum level in this participants